ANALISIS IMPLEMENTASI PERATURAN DAERAH KOTA SERANG NOMOR 12 TAHUN 2020 TENTANG PENYELENGGARAAN KETENTRAMAN, KETERTIBAN UMUM DAN PERLINDUNGAN MASYARAKAT (Studi Kasus: Pkl Di Jembatan Aria Wangsakara Kota Serang) - Oktaviani, Nadila; Hartoko, Gatot; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Public order and the use of public space are crucial issues in Serang City, especially in the Aria Wangsakara Bridge area. This situation causes aesthetic problems for the city, as well as social unrest, reflecting the ineffective implementation of policies in the field. This study is based on Van Meter and Van Horn’s policy implementation theory, which identifies six variables in policy implementation, to assess the extent to which Local Regulation No. 12 of 2020 has been effectively implemented and to identify factors that support or hinder its implementation. This study uses a descriptive qualitative approach. Data collection methods were conducted through interviews, observations, and documentation. Informants involved included the Serang City Satpol PP apparatus, Banjar Agung Village, the Head of RW, and street vendors at the Aria Wangsakara Bridge. The results of the study show that the implementation of the local regulation has not been optimal. The main obstacles include the lack of socialization of the policy to the community, the lack of human resources and supporting facilities, weak coordination between agencies, and inconsistency in the enforcement of sanctions. Although there has been a persuasive approach from the authorities, the results have not been strong enough to bring about a comprehensive change in attitude among street vendors. To improve the effectiveness of the policy, it is necessary to strengthen the capacity of implementers, adopt a participatory approach, and provide alternative locations.